2015
DOI: 10.1039/c5ra10549h
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics and bioavailability of intranasal and rectal midazolam formulations relative to buccal administration in rabbits

Abstract: The rectal and intranasal formulations under current development demonstrated comparative potential for administering midazolam in treating seizures in a medical emergency service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Based on the published values of butorphanol, midazolam, and dexmedetomidine Vd of 10.8 (Portnoy & Hustead, 1992), 4.3 (Odou et al, 1999, and 1.2 (Geyer, 1999) L/ Kg, respectively, the Vd/F values that we found in our study suggest that F was correspondingly 77%, 66.1%, and 18.8% for these three drugs. Interestingly, this value of midazolam TN-bioavailability is close to the one reported by Zhuang et al (2015). In addition, Iirola et al (2011) reported low values of TN-bioavailability for dexmedetomidine in humans.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Based on the published values of butorphanol, midazolam, and dexmedetomidine Vd of 10.8 (Portnoy & Hustead, 1992), 4.3 (Odou et al, 1999, and 1.2 (Geyer, 1999) L/ Kg, respectively, the Vd/F values that we found in our study suggest that F was correspondingly 77%, 66.1%, and 18.8% for these three drugs. Interestingly, this value of midazolam TN-bioavailability is close to the one reported by Zhuang et al (2015). In addition, Iirola et al (2011) reported low values of TN-bioavailability for dexmedetomidine in humans.…”
supporting
confidence: 84%
“…Interestingly, this value of midazolam TN‐bioavailability is close to the one reported by Zhuang et al . (). In addition, Iirola et al .…”
mentioning
confidence: 99%